Dynamic communication performance of a Hierarchical 3D-Torus network - Rahman, M.M. Hafizur; Sato, Yukinori; Miura, Yasuyuki; Inoguchi, Yasushi (2011)
A Hierarchical 3D-Torus (H3DT) network is a 3D-torus network of multiple basic modules, in which the basic modules are 3D-mesh networks, has been proposed for efficient 3D massively parallel computers. The static network performance, the number of vertical links for 3D implementation, and the VLSI layout area of the H3DT network was investigated. It was shown that H3DT network has less number of vertical links with economic layout area, while keeping good network features. However, the dynamic communication performance has not been evaluated yet. In this paper, we evaluate the dynamic communication performance of the H3DT network under both uniform and non-uniform traffic patterns, and compare it with other networks. We found that under non-uniform traffic patterns, the H3DT yields high throughput and low latency, providing better dynamic communication performance compared to TESH, mesh, and torus networks. Also, we found that non-uniform traffic patterns have higher throughput than uniform traffic patterns in the H3DT network.